Euro-Mediterranean Financial Markets Reaction to Political Elections - Oueslati, Jihene Ghouli; Basty, Nadia; Klouj, Lamis (International Journal of Social and Administrative Sciences, 2021)
This paper studies a sample of Euro-Mediterranean countries to test the link of political-financial interdependencies. We focus specifically on the impact of the occurrence of national elections on the reaction of financial markets. We used the GARCH (1,1) model and the concept of the volatility multiplier to test our hypotheses. The results established that political elections have a significant impact on stock market performance and volatility for Euro-Mediterranean countries. We detected anomalous behavior in stock market returns. Stock market returns on election day and in the days following the election are inversely higher as uncertainty about the election outcome decreases. Investor uncertainty, combined with the consequences of the multiparty system in Euro-Mediterranean countries, leads to negative abnormal returns around elections. In terms of volatility, we found that the greater degree of uncertainty about the situation and the market disruption affected by the media and social networks increase volatility before election day.